Pharmacokinetics of Lornoxicam in rabbits after single intravenous bolus and intramuscular administrations - El-Mahmoudy, Abubakr (International Journal of Pharmacology and Toxicology, 2016)
The pharmacokinetics of lornoxicam (a non-steroidal anti-inflammatory drug) at a dose of 0.4 mg/Kg body weight was evaluated after single intravenous (i.v.) and intramuscular (i.m.) bolus administrations in rabbits. An HPLC assay using pure lornoxicam base as a standard was used to measure its concentrations in plasma at prefixed time points up to 12 hours post administration. Following an i.v. bolus injection, the plasma concentration-time curves of lornoxicam were best represented by two-compartment open model. The drug was rapidly distributed and moderately eliminated with half-lives of distribution (t1/2Î±) and elimination (t1/2Î²) of 0.238 and 2.611 h, respectively. The volume of distribution was large with (Vdss) value of 1.499 L. The total body clearance (ClB) was 0.413 L/h. After i.m. bolus administration of the same dose, lornoxicam was moderately and completely absorbed in rabbits with an absorption half-life (tÂ½ab) of 1.228 h with peak plasma concentration (Cmax) of 0.463 Î¼g/mL attained at 1.512 h (Tmax) and systemic bioavailability of 99.79%. The elimination half-life following i.m. administration was 2.283 h. The extent of plasma protein binding percent was 98.9%. The study recommends the use of lornoxicam in rabbits because of its good pharmacokinetic profile indicated by good absorption, bioavailability and plasma concentrations.